The Principle Of Jurisdiction Over Jurisdiction In International Arbitration - علي , غسان; سليمان, بتريسيا (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The principle of the arbitral tribunal’s competence by adjudicating the validity of its jurisdiction, known as the principle of competence by jurisdiction is one of the most important principles in the framework of international arbitration and one of the most accurate. This principle has sparked many controversies despite its almost complete recognition of contemporary legal systems related to arbitration. Directly for the independence of the arbitration clause from the original contract, and the issue of transferring jurisdiction from formal courts to the agreement courts is one of the most important positive effects of the arbitration clause, as the arbitration tribunal replaces the judiciary in settling the dispute subject of the agreement, so there may not be a judicial vacuum as a result of giving up The judiciary is not performing its role, but rather it is replaced by the consensual judiciary chosen by the parties to adjudicate their dispute. The researcher relied on the descriptive and analytical approach of the legal texts and articles related to the principle of jurisdiction over the jurisdiction, the researcher reached many results, the most prominent of which were: The Syrian Arbitration Law approved the principle of competence with jurisdiction, where the Control Panel decides on the defenses related to its lack of jurisdiction, including the defenses related to the absence of an arbitration agreement or Its fall, nullity, or lack of inclusion of the subject of the dispute, and the positive effect of the principle of jurisdiction over jurisdiction in the jurisdiction of the arbitration judiciary in deciding on the issue of its jurisdiction alone, so that the state’s jurisdiction is not expected to be granted this power and the negative effect of adopting the principle of jurisdiction is the jurisdiction before state courts, where it is required that These courts shall refrain from considering or broadcasting any lawsuit that creates the arbitration clause or its validity, or directly on the subject of the dispute despite the apparent validity of this condition before the arbitrators say their word in it.